2021
DOI: 10.1039/d0sc06296k
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled low-molecular-weight gelator injectable microgel beads for delivery of bioactive agents

Abstract: We report microgel beads with diameters of ca. 800 nm based on interpenetrating networks of a low-molecular-weight gelator and a polymer gelator, and demonstrate their use as heparin delivery vehicles to enhance stem cell growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 64 publications
0
24
0
Order By: Relevance
“…Work to explore this is currently in progress. Given the ability to scale these beads down to the microscale, as we recently reported [5c] and the ability of this LMWG to control the release of bio‐active agents, [25] these mobile systems might also have applications in spatially resolved nanomedicine.…”
Section: Discussionmentioning
confidence: 99%
“…Work to explore this is currently in progress. Given the ability to scale these beads down to the microscale, as we recently reported [5c] and the ability of this LMWG to control the release of bio‐active agents, [25] these mobile systems might also have applications in spatially resolved nanomedicine.…”
Section: Discussionmentioning
confidence: 99%
“…We note that, with approximately 3 mm diameter, the beads reported here are too large for most local/systemic applications, which would better make use of injection as a delivery mode. However, we have recently demonstrated the potential to develop injectable microgels from this type of system, [9] and we therefore reason that statin‐loaded injectable microgel beads might be achievable. Such systems would be potentially transformative in injectable local and systemic delivery, and work towards this goal is currently a key target in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…We have also recently used this approach to generate smaller injectable microgel beads with diameters of about 800 nm, and shown that such microgels can release bioactive agents to enhance tissue growth. [9] With the goal of controlled drug delivery, we have previously been interested in multicomponent hydrogels. [10] As a result, we decided to develop gel beads with stimulus responsiveness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These various polymers establish complex 3D networks of intermolecular interactions between building blocks to form macroscopic objects. Besides polymers, low-molecular-weight gelators (LMWGs) (generally <2000 Da) are of great interest because the associated gelators have intrinsic self-assembly ability to form different morphologies of fibers, rods, ribbons, and nanotubes, which could be used to build attractive tools for various biomedical applications on account of their high biocompatibility and low toxicity ( Nolan et al, 2017 ; Ramin et al, 2017 ; Piras et al, 2021 ). Among the LMWGs, self-assembly peptide-based hydrogels are well known and have been the subject of many studies because the peptides are the most attractive building blocks, which can be readily controlled by changing the amino acid sequence of the peptides and by modifying the side chains of the peptides ( Frick et al, 2017 ; Fu et al, 2021 ; Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%